Kekristenan dan nasionalisme: Trayektori historis-biblis penyaliban Yesus dan kemerdekaan Indonesia - Parihala, Yohanes (KURIOS, 2024)
This article aims to emphasize that being Christian and being Indonesian are a manifestation of the Christian faith. The methodological approach used to explain it is trajectory history. The historical traces of Indonesia's struggle for independence, especially its nationalism movement, can be compared in a historical analysis with the experience of the colonialization of the Jews, the ministry of Jesus, and His crucifixion. The crucifixion' Jesus, which had occurred at the time of the colonialization of Jews, is the center of Christian preaching. Both the Jewish community and the Indonesian people had the same experience of colonialism in different eras and different powers. Finally, I urge that if the crucifixion of Jesus is interpreted as a history of redemption and the revelation of God's will, Indonesian Christians as disciples of Jesus are called to take part in developing the Indonesian nation. Indonesian Christians are an integral part of the nation.